Urticaria and its Update Management - Sikdar, TK; Ali, CM; Ahmed, N; Hoque, AKMR; Parvez, Z; Kamal, SMB (Bangladesh Medical Journal, 2011)
Key words: urticaria; update management DOI: 10.3329/bmj.v39i2.7036 Bangladesh Medical Journal 2010, 39(2) pp.40-44